Pelatihan pembuatan media tanam sayur dengan Teknik Hidoponik Sistem Deep Flow Technique (DFT) di Kalangan Pelajar Kabupaten Lamandau - Ismoyojati, Roni; Hidayat, Rahmat (LPMP Imperium, 2024)
The conversion of agricultural or plantation land to non-agricultural has reduced the area of land that can be utilized by the community to meet their food needs. The aim of the training activities for making vegetable growing media using the hydroponic technique of the DFT system among students in Lamandau Regency is to become an alternative to appropriate technology that can be used to overcome land conversion problems. Students are chosen because they are agents of change now and in the future. The training method used in carrying out this activity is training with lectures and work demonstrations on making hydroponic DFT systems using planting media, as well as monitoring and evaluating the application of DFT. The result of this training activity is an increase in knowledge and skills for students regarding appropriate technology to overcome the problem of land conversion which is always increasing in the future as a preparatory step.